1976
DOI: 10.1007/bf00428982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fat vs. high carbohydrate feeding on the development of obesity in weanling ob/ob mice

Abstract: Mice with hereditary obesity (ob/ob) were fed isocaloric, isoprotein diets with varying proportions of carbohydrate-to-fat from the time of weaning to 18 weeks of age. Body weight, plasma glucose,and plasma insulin were determined at frequent intervals; body lipid and pancreatic insulin were determined at termination. Obesity developed when only carbohydrate was provided as caloric source (and in the presence of essential fatty acid deficiency), but obesity was greatly enhanced when 5% fat was added. Obesity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The present study extends previous observations (Chlouverakis, 1971 ; Lemonnier et al 1971 ;Genuth, 1976;Flatt & Bailey, 1982a) that available dietary carbohydrate is especially important in the hyperinsulinaemia of oblob mice, and additionally indicates that this action is augmented by combination with protein. The glucose-dependent effect of amino acids involves direct stimulation of pancreatic B-cells and indirect mediation presumably via neural pathways and the secretion of insulinotropic hormones from the gut and pancreatic A-cells Flatt et al 1982).…”
Section: Discussionsupporting
confidence: 91%
“…The present study extends previous observations (Chlouverakis, 1971 ; Lemonnier et al 1971 ;Genuth, 1976;Flatt & Bailey, 1982a) that available dietary carbohydrate is especially important in the hyperinsulinaemia of oblob mice, and additionally indicates that this action is augmented by combination with protein. The glucose-dependent effect of amino acids involves direct stimulation of pancreatic B-cells and indirect mediation presumably via neural pathways and the secretion of insulinotropic hormones from the gut and pancreatic A-cells Flatt et al 1982).…”
Section: Discussionsupporting
confidence: 91%
“…Obesity has been associated with the consumption of highcarbohydrate or high-fat diets [11,24,25]. However, few studies have focused on the effect of dietary protein on the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…High-fat diets promote the entrance of fatty acids from chylomicrons into adipocytes, increasing their accumulation as triglycerides. On the other hand, high carbohydrate diets stimulate adipocyte lipogenesis, also increasing the amount of triglycerides in the lipid droplets of adipocytes [11,12]. However, it has been shown that only a limited amount of triglycerides can be stored in the adipose tissue of each individual.…”
Section: Introductionmentioning
confidence: 99%
“…He next studied these mice from the period before weaning to better identify the mechanism leading to diabetes and concluded that the underlying obesity and hyperphagia could be related to a genetically determined hypothalamic disturbance (5). Saul followed this work with an examination of exposure to high-fat and high-carbohydrate diets on the development of obesity in this mouse model and showed that the combined exposure to carbohydrate and fat in the diet led to the greatest amount of obesity (6).…”
Section: Research On Type 2 Diabetes and Obesitymentioning
confidence: 99%